Lending rate and commercial bank lending in Nigeria - Lateef Adewale Yunusa; Mayowa Ebenezer Ariyibi; Kehinde Isiaq Olaiya; Tolulope Oyakhilome Williams (Economic Review: Journal of Economics and Business, 2021)
The increase in the lending rate in Nigeria has affected the borrowers in the financial system and it has invariably reduced the pace of economic activities in the country. Such a situation created the need to examine the impact of the lending rate on bank lending in Nigeria. The study made use of ex-post facto research design. The data collected from the Central Bank of Nigeria Statistical Bulletin in the period 1981-2018 were subjected to Autoregressive Distributed Lag (ARDL) method of regression analysis. The analysis included the macroeconomic variable growth of bank lending, which is a proxy for bank lending, and the independent variables: lending rate, deposit growth, foreign exchange rate, liquidity rate, money supply, and GDP growth. The findings revealed there is a long-run relationship among the variables of the study. It was also discovered that the lending rate and liquidity ratio are inversely related to the growth of bank lending. Deposit growth and money supply both have a positive significant impact on the growth of bank lending. The monetary authorities should encourage banks to attract more deposit as this has a significant impact on the credit ability of the banks. A periodic review of the lending rate and liquidity ratio of the banks in the economy should also be carried out as these have a significant impact on the lending in the economy. Future researchers could extend the research by carrying out a cross country study in order to ascertain whether these variables will generate the same or a contradicting result.
Keywords: E43; E51; G21; C32; 330; lending rate; bank lending; ARDL